2006
DOI: 10.1007/s10067-006-0225-2
|View full text |Cite
|
Sign up to set email alerts
|

Delayed diagnosis of systemic lupus erythematosus due to lack of competency skills in musculoskeletal examination

Abstract: Deficiencies in musculoskeletal (MSK) examination skills among internal medicine residents can cause serious outcomes. We report a case of systemic lupus erythematosus with active arthritis where the diagnosis was delayed for 7 days after hospital admission due to the lack of basic skills in MSK examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Some studies have shown the effectiveness of computerbased modules in teaching performance of the musculoskeletal PE 12,13 , of the use of trained patients as teachers 14 , and of teaching 15 of core skills to medical students by medical professionals other than faculty. Research dealing with training at the residency level comes mainly from physiatry 16,17 and rheumatology 18,19 and further highlights the need for improvement.…”
mentioning
confidence: 99%
“…Some studies have shown the effectiveness of computerbased modules in teaching performance of the musculoskeletal PE 12,13 , of the use of trained patients as teachers 14 , and of teaching 15 of core skills to medical students by medical professionals other than faculty. Research dealing with training at the residency level comes mainly from physiatry 16,17 and rheumatology 18,19 and further highlights the need for improvement.…”
mentioning
confidence: 99%
“…2) On the party spirit education of party member: theory to guide the direction of the party, founding of Marx's theory education, we should from the thought highly of building the party (Almoallim, Khojah, Allehebi, & Noorwali, 2007). College ideological and political education for college students is the top priority of ideological and political education in colleges and universities and is an important measure of ideological construction and style building in Party building work.…”
Section: Main Work Of College Students Party Buildingmentioning
confidence: 99%
“…Despite the impact of MSK disorders on health care, rheumatological diseases are often overlooked or inadequately assessed by doctors [9][10][11][12] and there is a continuous neglect observed in musculoskeletal examination skills in clinical practice. Thus problems of patients with complaints about bones and joints are often ignored and underestimated by doctors.…”
Section: Deficiencies In Musculoskeletal Examination Skillsmentioning
confidence: 99%